Permanent Magnet Flux-Switching Machine, Optimal Design and Performance Analysis - Liviu Emilian Somesan; Emil Padurariu; Ioan Adrian Viorel (Advances in Electrical and Electronic Engineering, 2013)
In this paper an analytical sizing-design procedure for a typical permanent magnet flux-switching machine (PMFSM) with 12 stator and respectively 10 rotor poles is presented. An optimal design, based on Hooke-Jeeves method with the objective functions of maximum torque density, is performed. The results were validated via two dimensions finite element analysis (2D-FEA) applied on the optimized structure. The influence of the permanent magnet (PM) dimensions and type, respectively of the rotor poles' shape on the machine performance were also studied via 2D-FEA.